ANALISA BEBAN KERJA PENGEMUDI ANTAR JEMPUT PEGAWAI DENGAN METODE NASA TLX (STUDI KASUS SEKRETARIAT JENDERAL DPR RI) - Winurini, Sulis (Jurnal Aspirasi, 2015)
Since the reform of the bureaucracy implemented, effective working hours of employees are strictly enforced within the Secretariat General of the DPR RI. Indirectly, it increases the task challenge of the employee shuttle driver. Plus, the traffic conditions in Jakarta also increasingly congested and chaotic. With such conditions, the driver's workload increased and is expected to affect the quality of the performance. This study aims to measure the workload of employees the shuttle driver, so that researcher can get the information about the suitability between the task demands and the capacity of the driver. To meet these objectives, the type of research used is descriptive research, a study that aims to depict or describe the mental state of the driver's workload objectively shuttle bus to the NASA TLX method. The results obtained are the driver's workload is high, with a score of 66,75. Among the dimensions that exist in the work load, the dimension of the business is the highest level and dimension of frustration is on the lowest level. The age factor and the condition of the vehicle including the driver were contributing to the high workload of the driver. Therefore, recruitment of drivers, as well as repair and replacing the vehicle with the new one, are recommended.